ON A SWARM OF CRESEIS ACICULA RANG (PTEROPODA) IN THE KARWAR WATERS - Naomi, T S (Indian Journal of Fisheries, 2011)
The pteropods represented by Creseis acicula, Diacria sp. and Cavolinia sp. occurred occasionally in the zooplankton samples collected from the fishing grounds of the Karwar region. Generally the frequency of occurrence of C. acicula was greater than those of the others during the years 1980- ’82. The number of specimens of C. acicula per sample used to be a few and never exceeded 7,216 recorded on 10-4-1980 until an unusually large number 140,636 was observed in a surface haul of zooplankton on 16-10-1982.